Architectural sustainability on the impacts of different air-conditioning operational profiles and temperature setpoints on energy consumption: comparison between mosques with and without HVLS fan in the City Center Mosques - Mohamed, Nur Amalina Syairah; Shari, Zalina; Dahlan, Nur Dalilah; Idowu, Ibiyeye Aminat (University of Malaya, 2021)
The use of air-conditioning (AC) in conjunction with high-volume, low-speed (HVLS) fans has become a trend in retrofitted mosque buildings in Malaysia to improve thermal comfort conditions. However, the energy impact of operating AC and HVLS fan simultaneously is unknown. This study compares the annual energy consumptions between mosques with and without HVLS fan installed and investigates the optimum temperature setpoints and operational profile to improve the mosques' energy efficiency. The Building Energy Intensity (BEI) comparison did not clearly show the superiority between the two groups in terms of energy performance. The study found that both studied mosques could produce around 1-4.9% energy reduction when the AC temperature setpoint was increased by 1 ̊C and could result in the highest cost-saving of about 4.9% when the temperature was set at 27 ̊C. A 30-minute AC operation during each daily prayer, except Subuh, could save between 14.8-16.7% annual energy consumption and about 15.2-16.6% annual energy cost. The paper concludes that the selection of 24-27 ̊C temperature setpoints with a 30-minute AC operational profile during prayers time, considering Friday prayers and Ramadhan activities, produced 18.4-20.6% savings in energy cost. This study calls for reevaluations of AC temperature setpoints configuration standards and operational characteristics in mosque buildings to reduce energy consumption. This paper contributes to the development of future energy standards for mosque designs and operations in Malaysia.